2023
DOI: 10.1177/14550725231202066
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the early influence of COVID-19 in an analysis of the immediate implementation of Minimum Pricing for Alcohol on drinkers in Wales

Katy Holloway,
Marian Buhociu,
Shannon Murray
et al.

Abstract: Background: The Welsh Government has commissioned a number of projects to consider the influence their implementation of Minimum Pricing for Alcohol (MPA) legislation in March 2020 had on the alcohol consumption and related behaviours of drinkers. Given the MPA's overlap with the COVID-19 pandemic and its related lockdown measures and restrictions, this rapidly became a story about the early impact of COVID-19 as it did MPA. This paper captures the core thematic messages from this specific strand of work, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Doris Ochterbeck et al (2024) explored how addiction researchers view the implications of brain-based explanations of addiction and found that a main concern is a possible neglect of non-biomedical factors. The implementation of Minimum Pricing for Alcohol legislation in Wales in March 2020, which has thus far had little influence on drinking patterns and was overshadowed by the effects of the COVID-19 pandemic, shows a study by Holloway et al (2024) . Justina Kievišienė (2024) explored the attitudes of Lithuanian social workers towards people with alcohol use problems and found that although social workers understand their professional responsibilities, their motivation and dedication to work are low.…”
Section: In This Issuementioning
confidence: 99%
“…Doris Ochterbeck et al (2024) explored how addiction researchers view the implications of brain-based explanations of addiction and found that a main concern is a possible neglect of non-biomedical factors. The implementation of Minimum Pricing for Alcohol legislation in Wales in March 2020, which has thus far had little influence on drinking patterns and was overshadowed by the effects of the COVID-19 pandemic, shows a study by Holloway et al (2024) . Justina Kievišienė (2024) explored the attitudes of Lithuanian social workers towards people with alcohol use problems and found that although social workers understand their professional responsibilities, their motivation and dedication to work are low.…”
Section: In This Issuementioning
confidence: 99%